Realizing the Trinity of Pancasila Justice: A Socio-Legal Study of a Community-Based Conflict Resolution - Ahmad Saparwadi; FX Joko Priyono; Ro’fah Setyowati (Jurnal Mulawarman Law Review, 2025)
Public conflicts involving both religious and economic sentiments, such as the case of the "religious seller" (Gus Miftah) and the "ice tea seller," (Sunhaji) present unique challenges that are often difficult to resolve through formal law. This study aims to analyze the settlement of cases between religious sellers and iced tea sellers based on Pancasila justice. The type of research used is normative-empirical research with a philosophical, conceptual, and socio-legal approach. The legal materials used are primary and secondary, which are then analyzed using qualitative descriptive techniques. The results of the study show that the settlement of cases between religious sellers and ice tea sellers reflects the values of Pancasila justice because it is able to provide substantive justice for the parties. This is based on the mechanism of case settlement through deliberation, which is part of the values of divine justice and humanity and also society, one of which is mutual forgiveness between the two parties. The religious seller received social sanctions from the community for his insults, which were considered a warning from God and the community. Meanwhile, the iced tea seller received rewards from God and society in the form of material and immaterial support for what he experienced. Thus, this case represents justice for both parties in the context of Pancasila justice, which encompasses divine, humanitarian, and social justice.